Optimalisasi Media Sosial LKK Tamansari melalui Pelatihan Content Pillar - Rohimakumullah, Muhammad Al Assad; Pasaribu, Anggian Lasmarito; Buana, Gendra Wisnu; Debora, Elvi Bertha (Universitas Prof. Dr. Moestopo (Beragama), 2025)
Tamansari Subdistrict, located in Bandung Wetan District, Bandung City, has considerable socio-economic potential and a strategic position in the city center. However, the Tamansari Subdistrict Partnership Institution (Lembaga Kemitraan Kelurahan/LKK Tamansari) faces challenges in social media management, particularly due to the lack of a consistent brand image and a structured content strategy. This situation has reduced the effectiveness of public communication and institutional image-building. This community service program aims to strengthen the capacity of LKK Tamansari to manage social media content professionally through an understanding of content pillar concepts and institutional brand image development. The program targets administrators and members of LKK Tamansari as key actors in subdistrict-level public communication. The activities were conducted using a Participatory Action Research (PAR) approach, including preliminary research, training material development, interactive workshops, content creation simulations, and evaluation through participant presentations. The results demonstrate a significant improvement in participants’ understanding, with most participants able to independently demonstrate social media content planning. Furthermore, participants showed increased confidence and greater awareness of social media’s potential as a tool for promoting local MSME products. This program contributes to the downstream application of research outcomes in empowering local institutions through digital communication.